Valuación en el sector inmobiliario aplicando el principio de mayor y mejor uso: una propuesta de metodología para evaluar - Martínez Miranda, Irina (2020)
The purpose of this work is to analyze how the use assigned to a property is an element that fundamentally affects its value. This idea is based on the concept of Major and Best Use used in real estate valuation, however, it is important that real estate investors and developers have knowledge of it and how, through this idea of use as an originator of value they can make purchase decisions and project planning that will result in maximum financial productivity. To demonstrate this, a study was conducted on a property in Mexico City that is used as an industrial warehouse with offices. The study consisted in proposing alternative use scenarios and verifying through discounted cash flows if there is a change in the final value of the property. The results show that there may be a significant gap from the lowest value obtained with respect to the highest, which would imply a significant loss in value for an investor or developer.